Experimental observation of nonspherically-decaying radiation from a rotating superluminal source - Ardavan, A; Hayes, W; Singleton, J; Ardavan, H; Fopma, J; Halliday, D (2004)
An experimental implementation of an oscillating, superluminal polarization current distribution that undergoes centripetal acceleration was constructed and tested. The emission from the experimental machine was found to be tightly beamed in both the azimuthal and polar directions. It was found that the beaming is frequency independent and has a sharply defined and unchanging geometry determined only by the speed and path of the moving distribution pattern. The intensity of the radiation at these angles was observed to decline more slowly with increasing distance from the source than would the emission from a conventional antenna.